2014
DOI: 10.1002/bjs.9523
|View full text |Cite
|
Sign up to set email alerts
|

In vitro model to study the biomaterial-dependent reaction of macrophages in an inflammatory environment

Abstract: Macrophages in an inflammatory environment in vitro still react in a biomaterial-dependent manner. This model can help to select biomaterials that are tolerated best in a surgical environment at risk of contamination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 27 publications
(51 reference statements)
2
21
0
Order By: Relevance
“…The use of biomaterials has become common in regenerative medicine. The reaction of primary human macrophages to biomaterials has been shown in vitro to be biomaterial specific, even when an inflammatory situation is simulated [18,19]. However, the person-dependent foreign body response has not been taken into account in these models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of biomaterials has become common in regenerative medicine. The reaction of primary human macrophages to biomaterials has been shown in vitro to be biomaterial specific, even when an inflammatory situation is simulated [18,19]. However, the person-dependent foreign body response has not been taken into account in these models.…”
Section: Discussionmentioning
confidence: 99%
“…Previous in vitro models have shown that culturing macrophages isolated from healthy donors on different biomaterials leads to a biomaterial-specific reaction [18] and that even in a contaminated in vitro model, surgical biomaterials still elicit differential reactions in macrophages [19]. These in vitro models did not take into account patient specific characteristics, such as age, smoking, diabetes or obesity.…”
Section: Introductionmentioning
confidence: 99%
“…e Re-combined culture: different cell types either from primary dissociations or cell lines are combined in known a specified ratio and cultured together. [116].…”
Section: Monocyte/macrophage Culturesmentioning
confidence: 95%
“…Minimal immune cell adhesion to microdevice surfaces leads to decreased macrophages being available to fuse into FBGCs. Regardless of the origin of the immune cells being tested (cell line or primary source), the surface chemistry of the material determines the ability of leukocytes, monocytes and macrophages to attach and spread on it [116]. Immune cell attachment and reactions to a surface are modified by the ability of proteins to first adhere the surface [67].…”
Section: Monocyte/macrophage Culturesmentioning
confidence: 99%
“…Moreover, the inflammatory environment, simulating bacterial infection, increased proinflammatory cytokine production by macrophages cultured with PET. In contrast, macrophages cultured with polypropylene responded with CCL18 production and demonstrated a low pro/anti-inflammatory cytokine ratio [51]. These studies suggested that choice of biomaterial may be critical when implant-associated infection is possible.…”
Section: Macrophage Responses To Implantsmentioning
confidence: 97%